Cataclysmic variables in globular clusters and low mass X-ray binaries - Machin, G; Machin, Graham (1990)
An introduction is given to cataclysmic variables (CVs), low mass X-ray binaries (LMXBs) and globular clusters. The radio properties of LMXBs are reviewed. I present optical spectroscopy and photometry of the globular cluster CV candidates, V4 in M30, V101 in M5, the CV candidates in M71 and of the LMXB 4U06144-09. VLA observations of the globular cluster X-ray sources in NGC7078, NGC6712, NGC6624 and NGC1851 and a "snapshot" of the galactic LMXB 4U2129+47 are presented. The quiescent colours of V4 indicate that its orbital period is <5 hours. Its radial velocity, quiescent and outburst magnitudes show that it is probably not a cluster member. A hump in the light curve of V101, its quiescent colours, outburst magnitude and the results of quiescent state time resolved spectroscopy are all consistent with an orbital period of ~5-8 hours. V101 is the only CV whose photometric properties are compatible with cluster membership. Spectroscopy of the two brightest CV candidates in M71 shows that they are subdwarf B stars. The nature of the remaining candidates is discussed. Radio counterparts to the X-ray sources in NGC7078 and NGC6712 are discovered. The observed emission is interpreted in terms of the synchrotron emission mechanism. Upper limits are placed on radio emission from the X-ray sources in NGC6624 and NGC1851 and from the galactic LMXB 4U2129+47. 4U0614+09 displays photometric variability on two timescales; 10 days and 1 hour. The former is interpreted as a precessing accretion disc whilst the latter could be either long timescale QPO or the orbital period. The optical spectrum is unusual because it only displays the Bowen blend (λ4640-4660) emission feature not He II λ4686. Possible explanations for this behaviour are discussed. Simultaneous optical and X-ray photometry shows that the optical flux was anticorrelated with the X-ray emission.